Equitable Education: Enhancing Academic Skills and Confidence Through a First-Year Online Module - Brooke E. Harris-Reeves; Andrew G. Pearson; Barbara J. Hadley; Helen M. Massa (JANZSSA)
Since 2008, higher education (HE) policies that aimed to diversify university student recruitment have increased enrolments from equity backgrounds. Supporting these students during their transition to university has been prioritised with the aim of enhancing retention, completion, and support for their future employment outcomes. Low student retention or program completion rates may impact federal government funding models and HE institutional reputations. Thus, a wide range of implemented strategies have sought to support HE success for all students, including those from equity backgrounds. Students transitioning to HE have different academic experiences and expertise. Thus, the online module, known as Skills for Academic Success (SAS), developed in this study was introduced to promote an enhanced understanding of HE expectations and academic skills needed for success. The module was completed by commencing students during the initial weeks of their university enrolment. Students perceived that the SAS module significantly enhanced their transition to HE, their understanding of university expectations, bolstered their academic confidence, and honed their study skills for success. This study showed that adaptive online modules can engage and assist students, especially those from diverse and equity-rich backgrounds, supporting them to develop a comprehensive grasp of HE academic expectations and essential academic skills. Student feedback highlighted that the resource prepared them for success as they embarked on their academic journey in the unfamiliar territory of HE.